Resposta imune intestinal de camundongos geneticamente deficientes em complexo de histocompatibilidade principal (MHC classe I ou II) infectados por Strongyloides venezuelensis - Rodrigues, Rosângela Maria (2008)
In rodents and in humans, Strongyloides sp. infection induces an immune response characterized by tissue eosinophils, mastocytosis, production of Th2 cytokines and antibodies. Accordingly, in this study, we investigated the immune response against Strongyloides venzuelensis infection in major histocompatibility complex (MHC) class I or class II deficient mice. Wild-type C57BL/6 (WT), MHC I-/- and MHC II-/- mice were individually inoculated with 3.000 larvae (L3) de S. venezuelensis and sacrificed on 50, 80, 130 and 210 days post-infection (p.i.). The infectivity rate was determined by eggs/g of feces counted, number of adult worms recovered from small intestine and fecundity rate. The samples of small intestine were routinely processed an stained with hematolxilin-eosin, toluidin blue and PAS-alcian blue for identification of eosinophils, mast cells and globets cells respectively. Levels of IL-4, IL-5, IL-12 e IFN-γ were quantified in homogenates from the small intestine and sera by ELISA. Levels of Strongyloides-specific IgM, IgA, IgE, IgG total, IgG1 e IgG2a were quantified in sera of mice infected with S. venezuelensis and in non-infected animals by ELISA. Blood samples were collected for total blood cell and differential counts. Samples of blood and small intestine were collected. It was demonstrated that MHC II-/- animals are more susceptible to Strongyloides infection by presenting elevated number of eggs recovered in the feces and delay in elimination of adult worms when compared to WT and MHC I-/- mice. Histopathological analysis revealed that MHC II-/- had a mild inflammatory infiltration in the small intestine with reduction in tissue eosinophilia mast cells and globets cell. These mice also presented significantly low numbers of eosinophils and mononuclear cells in the blood, together with reduced Th2 cytokines in small intestine homogenates and sera when compared to WT and MHC I-/- animals. Additionally, parasite-specific IgM, IgA, IgE, total IgG and IgG1 were also significantly lowered in the sera of MHC II-/- infected mice, while a discrete increase in the levels of IgG2a could be observed in comparison to WT or MHC I-/- infected mice. Altogether, these data demonstrated that expression of MHC class II but not class I molecule is required to induce a predominant Th2 response and efficient control of S. venezuelensis infection. These results provided evidences for the mechanisms involved in the development of systemic disseminated and potentially fatal forms of strongyloidiasis in immunocompromised hosts.